On the use of varying die angle for improving the resistance to hydrogen embrittlement of cold drawn prestressing steel wires. (January 2015) - Toribio, J.; Lorenzo, M.; Vergara, D.
Highlights: Die geometry affects residual stress–strain distributions after wire drawing. Hydrogen diffusion and embrittlement are governed by residual stress–strain fields. Die design with double angle improves the resistance to hydrogen embrittlement. The second die angle must be lower than the first one (as low as possible). The second die angle plays a more relevant role than the first one. Abstract: Residual stresses produced by cold drawing are an undesirable effect of the non-uniform plastic strain distribution generated during the conforming process used for obtaining prestressing steel wires. Among the diverse parameters of the process influencing the residual stress generation, one of the most relevant is the geometry of the drawing die and, in particular, the inlet die angle. Wires drawn with die angles as low as possible will exhibit a lower and more homogeneous plastic strain state and, therefore, a smaller and more uniform residual stress state. Thus the hydrogen embrittlement (HE) susceptibility of such wires is also lower, thereby enlarging the life in service of these components. In this paper an innovative design of the drawing die is proposed using two consecutive angles (i.e., varying die angle) for reducing the residual stress and strain state in the cold drawn wires and, consequently, for improving the resistance to HE of prestressing steel wires.